Review of: Shah, Prakash (ed) (2007). Law and Ethnic Plurality. Socio-Legal Perspectives. Martinus Nijhoff Publisher: Leiden and Boston. - Iker Barbero (Sortuz)
The academic interest that Prakash Shah (Senior lecturer in Queen Mary University of London) has shown towards diasporic communities has turned him into a salient figure in the study of Law and Immigration issues. Law and Ethnic Plurality: Socio-legal perspectives is an example of this rigorous academic  trajectory.